Sistema de análisis de patrones implementado en FPGAs para el estudio experimental de los ligamentos en la articulación - Raygoza Panduro., J. J.; Ortega Cisneros., Susana; Bonsfills., Nuria; Núñez., Ángel; Gómez Barrena., E. (Revista Mexicana de Ingenieria Biomedica, 2009)
The damage of the Previous Crossed Ligament (LCA) has been one of the most widely and varied studied pathologies. We have experimented with both direct and indirect variable forms, which define the concept of instability produced by this injury. Due to the difficulty in measuring this phenomenon, a wide range of methodologies have been proposed in order to measure it. The tension study focuses on the specific structures needed for stability and mobility, comparing healthy and injured joints as well as considering treatment and rehabilitation. This article presents the implementation of an electronic monitoring system of tension-deformation of ligaments of the joint and of a patterns recognition system. The system is composed of strain gauge sensors that detect ligament tension-deformation changes during movements, forming typical patterns which are classified by an electronic circuit consisting of a microprocessor with an arrangement of neural networks embedded in a FPGA reconfigurable device.